Chronic Disseminated Histoplasmosis in an Immunocompetent Man Presented as Bilateral Adrenal Masses with Partial Adrenocortical Insufficiency - A Rare Condition (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Bilateral adrenal masses caused by histoplasmosis is a rare condition. To our knowledge this is the first case report of   bilateral adrenal enlargement by histoplasmosis in  Bangladesh. We report a case of 75 years old man who presented with  low grade fever, night sweating, anorexia and progressive  weight loss for 9 months prior to admission in Square Hospital. Clinical profile was unremarkable apart from low   grade fever (with maximum temperature recorded up to 101ºF) and low blood pressure with significant postural  drop. Plasma cortisol (morning and evening) and glucose were normal but short ACTH stimulation test revealed low   plasma cortisol response. Abdominal ultrasound gave a definite clue of left adrenal mass which was later found as bilateral adrenal masses of significant size by abdominal CT scan. Initially Gomoris Methenamine Silver (GMS) stain of CT guided FNAC of the left adrenal mass showed small budding yeast morphologically consistent with histoplasmosis. A second CT guided FNAC of both adrenal masses also showed similar findings which was finally confirmed by fungus culture as Histoplasma capsulatum. The patient was then treated with injection amphotericin-B followed by oral itraconazole and fludrocortisone and he responded well DOI: http://dx.doi.org/10.3329/jbcps.v29i4.11345 J Bangladesh Coll Phys Surg 2011; 29: 235-240